Model Pengembangan Strategi Manajemen Terhadap Peningkatan Manajemen Mutu Pendidikan Di SDN 9 Baru- Baru Tanga - M. Aris Akin; Putrama Riawana; Nurul Muwaffiqah (Institut Nalanda, 2023)
Education is an investment in the development of human resources, where increased skills and abilities are believed to be a supporting factor for human efforts in navigating a life full of uncertainties. it is within this framework that education is needed and seen as a basic improvement need for people who want to progress, this is the case for Indonesian people who have a very wide area.